Modified gradient dynamic approach to the tensor complementarity problem. (3rd March 2020) - Wang, Xuezhong; Che, Maolin; Qi, Liqun; Wei, Yimin
ABSTRACT: Nonlinear gradient dynamic approach for solving the tensor complementarity problem (TCP) are presented. Theoretical analysis shows that each of the defined dynamical system models ensures the convergence. The computer-simulation results further substantiate that the considered dynamical system can solve the TCP.